Structures and characteristics of the alloyed, microalloyed and modified hypoeutectic gray cast iron - A. N. Suchkov; O. I. Karabits; E. V. Kuznetsov; V. N. Pustovoit; V. M. Malov (Литьë и металлургия)
There is worked out and incorporated the calculation algorithm and packet of application programs for control of characteristics and structure of hypoeutectic gray cast iron of cupola heat (rough and low-alloyed) by means of optimization of the mixture components, chemical composition of alloy and its modification and microalloying.